Effect of Boron on Hot Ductility and Room-Temperature Tensile Properties of Microalloyed Steels with Titanium and Niobium - Qi Li (Materials, 2019)
Effect of boron on the hot ductility and room-temperature tensile properties of Ti-Nb-microalloyed steels containing 0.071 wt.% carbon was studied. The thermal stress and thermal strain of continuous casting billets during cooling were simulated via hot tensile tests at the deformation rate of (6 mm/11,000)/s, and the hot ductility of different microalloyed steels was evaluated according to the area reduction of hot tensile specimens. It was found that boron addition was beneficial to improve the hot ductility of continuous casting billets during straightening, and the reduction of area exceeded 60%. The addition of boron, as well as the removal of molybdenum and vanadium, can effectively lower the austenite-to-ferrite transformation temperature and restrain the formation of intergranular ferrite, so as to avoid the brittle zone. Moreover, the room-temperature tensile properties of the steels were explored at different cooling rates after the rolling process. The results showed that as the cooling rate increased from 0.0094 to 0.13 °C/s, the amount of carbonitride precipitate gradually decreased, such as titanium carbide, leading to the relatively low tensile strength. On the other hand, the addition of boron, as well as the removal of Mo and V, promoted the formation of bainite and acicular ferrite, playing an important role in structure strengthening, and compensated for the decrease of tensile strength caused by the low precipitation strengthening.